Ultraestrutura, expressão gênica e imunomarcação da caspase-3, XIAP, IGF-1R do córtex cerebelar de ratos UChA (consumidores voluntários de etanol) - Oliveira, Suelen Alves de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Introduction: The cerebellum is susceptible to the harmful effects of ethanol in acute or chronic exposures at different ages, which may cause motor, learning and cognitive disorders and promote apoptotic cell death (PCD) as well. Our objective was to evaluate apoptosis in Golgi and Purkinje neurons and in granular cell disease of the cerebellum of adult rats of the type UChA. Methodology: The rats were divided in two experimental groups (20 rats per group): a control group, consisting of abstinent UChA animals and the experimental group, formed by UChA rats, volunteers consumers of 10% ethanol (˂ 2g ethanol / kg weight body / day). From 65 day-age to the 120 day-age, the animals received 10% ethanol solution. After 120 days, the rats were anesthetized and prepared for euthanasia. The cerebellum was then analyzed by transmission electron microscopy (TEM), immunohistochemistry to apoptosis, caspase-3 (pro-apoptotic), XIAP (anti-apoptotic) and IGF-1R in Golgi, Purkinje neurons and granular as well. It was also evaluated by RT-PCR (Reverse transcription polymerase chain reaction) the regulatory genes caspase-3, XIAP and IGF-1R in the cerebellar cortex of groups. Results: The UChA animals showed accumulation of lipid droplets, presence of electron-nuclei in granule neurons and Purkinje, disorganization of the medullary body of the cerebellum with some changes in the myelin sheath of the cortex. It was also identified significant increase in the Immunostaining caspase-3 and XIAP in Purkinje neurons and granular. The DNA fragmentation was significant in Purkinje cells. The IGF-1R didn't have any change though. There were no significant differences in the formulation of caspase-3 genes, XIAP and IGF-1R. Conclusion: Ethanol induces apoptosis in granular and Purkinje cells of the cerebellum of adult UChA rats

Introdução: O cerebelo é suscetível aos efeitos lesivos do etanol em exposições agudas ou crônicas, em diferentes idades, podendo ocasionar alterações motoras, de aprendizado, cognitivas e favorecer a morte celular apoptótica. Nosso objetivo foi avaliar a apoptose nos neurônios de Golgi, Purkinje e células granulares do cerebelo de ratos adultos da variedade UChA. Metodologia: Os ratos foram divididos em dois grupos experimentais (20 ratos por grupo): um grupo controle, composto de animais UChA abstinentes e o grupo experimental, formado por ratos UChA, consumidores voluntários de etanol a 10% (˂ 2g etanol/Kg peso corpóreo/dia). Dos 65 dias aos 120 dias de idade, os animais receberam solução de etanol a 10%. Aos 120 dias, os animais foram anestesiados e preparados para eutanásia. O cerebelo foi então analisado por microscopia eletrônica de transmissão (MET), imunoistoquímica para apoptose, caspase-3 (próapoptótica), XIAP (antiapoptótica) e IGF-1R nos neurônios de Golgi, Purkinje e granulares. Avaliou-se também por RT-PCR os genes reguladores da caspase-3, XIAP e IGF-1R no córtex cerebelar dos grupos estudados. Resultados: Os animais UChA mostraram acúmulo de gotas lipídicas, presença de núcleos eletrodensos nos neurônios granulares e de Purkinje, desorganização do corpo medular do cerebelo com alterações na bainha de mielina no córtex cerebelar. Identificou-se também aumento significativo na imunomarcação de caspase-3 e XIAP nos neurônios de Purkinje e granulares. A fragmentação do DNA foi significativa nas células de Purkinje. O IGF-1R não apresentou alterações. Não houve diferenças significativas na expressão dos genes de caspase-3, XIAP, e o IGF-1R. Conclusão: O etanol induz apoptose nas células de Purkinje e granulares do cerebelo de ratos adultos UChA
Ultrastructure, gene expression and immunostaining caspase 3, Xiap, and igf-1r in the cerebellar cortex of ucha rats (Volunteer ethanol consumers)
Keywords: Cerebelo; Degeneração (Patologia); Alcoolismo; Apoptose; Proteinas - Analise; Expressão gênica; Cerebellum; Apoptosis